Interactions in the Agrobacterium-soybean system and capability of some Brazilian soybean cultivars to produce somatic embryos - Di Mauro, A. O.; Nobrega, JCM de; Di Mauro, SMZ; Collins, G. B. (Soc Brasil Genetica, 2000)
Twenty-five Brazilian soybean cultivars were studied for susceptibility to four strains of Agrobacterium tumefaciens (C58, Ach5, Bo542 and A281) and for their ability to produce somatic embryos. Twelve plants of each cultivar were inoculated in a greenhouse at 4-6 weeks of age, using 12 inoculation sites per plant. The number of galls formed on plants were counted 8-10 weeks after inoculation. To study ability to produce somatic embryos, immature cotyledons, 4-6 mm in length, were plated onto N10 medium for induction of somatic embryogenesis, using four Petri dishes with 20 cotyledons for each cultivar. The embryogenic tissues were transferred onto new N10 medium six times at 15-day intervals and the number of somatic embryos per cultivar determined. Significant interaction between soybean cultivars and A. tumefaciens strains was observed; the most virulent strain was A281. The opine type apparently had no effect on strain virulence, and the most embryogenic cultivars were IAS-5, Cristalina, FT-Cometa, IAC-7 and OC-3.